2022
DOI: 10.1172/jci157086
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting the DREAM complex enables proliferation of adult human pancreatic β cells

Abstract: Resistance to regeneration of insulin-producing pancreatic β cells is a fundamental challenge for type 1 and type 2 diabetes. Recently, small molecule inhibitors of the kinase DYRK1A have proven effective in inducing adult human β cells to proliferate, but their detailed mechanism of action is incompletely understood. We interrogated our human insulinoma and β cell transcriptomic databases seeking to understand why β cells in insulinomas proliferate, while normal β cells do not. This search reveals the DREAM c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 71 publications
0
32
0
Order By: Relevance
“…Repression of FOXM1 during aging is known to trigger dysfunctional mitotic machinery and contribute to aneuploidy-driven senescence, while cyclic FOXM1 expression delayed senescence and alleviated aging phenotypes in progeroid mice 52,53 . Recently, disturbing DREAM complex with small molecule kinase DYRK1A inhibitor have shown to improve proliferation of adult human pancreatic β cells 54 . In agreement with previous studies, we show that a broad range of genes repressed during senescence is connected to the DREAM complex and might be critical for cell cycle exit or mitotic decline.…”
Section: Discussionmentioning
confidence: 99%
“…Repression of FOXM1 during aging is known to trigger dysfunctional mitotic machinery and contribute to aneuploidy-driven senescence, while cyclic FOXM1 expression delayed senescence and alleviated aging phenotypes in progeroid mice 52,53 . Recently, disturbing DREAM complex with small molecule kinase DYRK1A inhibitor have shown to improve proliferation of adult human pancreatic β cells 54 . In agreement with previous studies, we show that a broad range of genes repressed during senescence is connected to the DREAM complex and might be critical for cell cycle exit or mitotic decline.…”
Section: Discussionmentioning
confidence: 99%
“…However, numerous biological targets have been studied in this context, including DYRK1A. Studies show that DYRK1A small molecule inhibitors induce human β-cell proliferation both in vitro and in vivo [ 54 , 78 , 114 , 115 , 116 , 117 , 118 ]. Several studies have demonstrated that DYRK1A overexpression attenuated β-cell proliferation through NFAT dysregulation, a transcription factor that transactivates cell cycle-activating genes and represses cell cycle inhibitor genes including other CMGC, cyclins and p57 ( Table 1 ) [ 30 , 68 , 114 , 115 ].…”
Section: Dyrk1a and Other Diseasesmentioning
confidence: 99%
“…Wang et al . 2 reported that they elucidated the regulation mechanism of pancreatic β cell proliferation, particularly via dual‐specificity tyrosine‐regulated kinase‐1a (DYRK1A) inhibition. The proliferation of pancreatic β cells has been thought to be mainly regulated by calcium ions.…”
mentioning
confidence: 99%
“…The DREAM complex consists of a MuvB core (retinoblastoma binding protein 4 (RBBP4) and LIN9, LIN37, LIN52, and LIN54) and additional components 4 , converting its function to either repressive or proliferative depending on the additional components. When the MuvB complex binds to its repressive partners, p130, p107, and E2F4 or E2F5, the DREAM complex is referred to as DREAM repressive form 2 . The key to forming the repressive version of the DREAM complex is the phosphorylation of LIN52 by the kinase DYRK1A.…”
mentioning
confidence: 99%
See 1 more Smart Citation